Factors predicting cardiac arrest in acute coronary syndrome patients under 50: A state-wide angiographic and forensic evaluation of outcomes. (October 2022) - Paratz, Elizabeth D.; van Heusden, Alexander; Smith, Karen; Brennan, Angela; Dinh, Diem; Ball, Jocasta; Lefkovits, Jeff; Kaye, David M.; Nicholls, Stephen J; Pflaumer, Andreas; La Gerche, Andre; Stub, Dion; et al.
Abstract: Background: An uncertain proportion of patients with acute coronary syndrome (ACS) also experience out-of-hospital cardiac arrest (OHCA). Predictors of OHCA in ACS remain unclear and vulnerable to selection bias as pre-hospital deceased patients are usually not included. Methods: Data on patients aged 18–50 years from a percutaneous coronary intervention (PCI) and OHCA registry were combined to identify all patients experiencing OHCA due to ACS (not including those managed medically or who proceeded to cardiac surgery). Clinical, angiographic and forensic details were collated. In-hospital and post-discharge outcomes were compared between OHCA survivors and non-OHCA ACS patients. Results: OHCA occurred in 6.0% of ACS patients transported to hospital and 10.0% of all ACS patients. Clinical predictors were non-diabetic status (p = 0.015), non-obesity (p = 0.004), ST-elevation myocardial infarction (p < 0.0001) and left main (p < 0.0002) or left anterior descending (LAD) coronary artery (p < 0.0001) as culprit vessel. OHCA patients had poorer in-hospital clinical outcomes, including longer length of stay and higher pre-procedural intubation, cardiogenic shock, major adverse cardiovascular events, bleeding, and mortality (p < 0.0001 for all). At 30 days, OHCA survivors had equivalent cardiac function and return to premorbid independence but higher rates of anxiety/depression (p = 0.029). Conclusion: OHCA complicates approximately 10% of ACS in the young. Predictors of OHCA are being non-diabetic, non-obese, having a STEMI presentation, and left main or LAD coronary culprit lesion. For OHCA patients surviving to PCI, higher rates of in-hospital complications are observed. Despite this, recovery of pre-morbid physical and cardiac function is equivalent to non-OHCA patients, apart from higher rates of anxiety/depression.